Irving Penn centennial - Hambourg, Maria Morris 1949-; Rosenheim, Jeff L. (The Metropolitan Museum of Art, 2017)
"Celebrating the centennial of Irving Penn's birth, this volume spans the entirety of his groundbreaking career. The introduction situates his work in the context of the various artistic, social, and political environments and events that affected the content of his photographs. The essays acquaint readers with Penn's primary subjects and campaigns, including early documentary scenes and imagery; portraits; fashion; female nudes; people of Peru, Dahomey (Benin), New Guinea, and Morocco; still lifes; and more"--Provided by publisher